PENGARUH KEPUTUSAN INVESTASI DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (PERUSAHAAN MANUFAKTUR SUBSEKTOR KOSMETIK DAN KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Kusmanto "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the effect of investment decisions and firm size on firm value. Where the independent variables in this study are investment decisions and company size and the dependent variable is the value of the Company.  This study uses secondary data in the form of company financial statements and annual reports annual report of cosmetics and household needs sub-sector manufacturing companies listed on the Stock Exchange in 2011-2017. Sampling using purposive sampling technique, which is used is 5 companies. Data analysis using simple linear regression analysis, multiple linear regression analysis, T test, F test and coefficient of determination test using SPSS 23 device.The results of the analysis show that the investment decision variable partially (t test) influences the firm value of the cosmetics sub-sector manufacturing companies and household needs listed on the Indonesia Stock Exchange, the variable size of the company partially (t test) influences the firm value in the subsector manufacturing company cosmetics and household needs listed on the Indonesia Stock Exchange. Simultaneous test results (test f) indicate the influence of investment decision variables and firm size on firm value in the cosmetics sub-sector manufacturing companies and household needs listed on the Indonesia Stock Exchange.  Keywords: Investment Decisions, Company Size, and Company Value